2016
DOI: 10.1002/pbc.26049
|View full text |Cite
|
Sign up to set email alerts
|

Response of Blue Rubber Bleb Nevus Syndrome to Sirolimus Treatment

Abstract: Sirolimus is safe and efficient for the treatment of BRBNS. Further prospective studies are needed to evaluate the long-term effectiveness of this drug. This is the first report that identifies a lymphatic component as part of BRBNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 13 publications
1
55
0
5
Order By: Relevance
“…While minimally invasive therapeutic techniques are beginning to be described, to the best of our knowledge, we report the first case of rapamycin use to obtain a rapid and sustained response in the treatment of pediatric DLs. Rapamycin has been used in the setting of other GI vascular malformations to reduce GI bleeding and has been shown to be effective in many such conditions . In such cases, rapamycin has been shown to inhibit endothelial signaling pathways and lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While minimally invasive therapeutic techniques are beginning to be described, to the best of our knowledge, we report the first case of rapamycin use to obtain a rapid and sustained response in the treatment of pediatric DLs. Rapamycin has been used in the setting of other GI vascular malformations to reduce GI bleeding and has been shown to be effective in many such conditions . In such cases, rapamycin has been shown to inhibit endothelial signaling pathways and lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For more significant hemorrhages or severe complications, surgical resection, endoscopic sclerosis, and laser photocoagulation have been proposed. Because of its anti‐angiogenic properties, some authors have reported the efficacy of mTOR inhibitors such as sirolimus . Unfortunately, effectiveness of the mTOR inhibitor could not be assess in our patient because of its early withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Physical abdominal examination was normal. The blood test revealed a nonregenerative normocytic anemia with hemoglobin at 7.3 g/dL (vs. 10 reticulocyte count at 35,420/mm. Platelet count was normal (320,000/mm 3 ).…”
Section: Case Reportmentioning
confidence: 99%
“…Recent clinical trials confirm that sirolimus is a safe and efficient for the treatment of BRBNS. Salloum et al (Salloum et al, ) showed that four children with BRBNS received sirolimus treatment, and the responses improved in all patients. The adverse effects of the drug in the cohort only consisted of mucositis in three patients and neutropenia in one patient.…”
Section: Sirolimus Therapy In Pediatric Overgrowth Diseasesmentioning
confidence: 99%
“…In our clinical experiences, the most common dosage of sirolimus treatment the BRBNS is 1.5–2 mg/m 2 per day, the therapeutic range of the drug is 5–10 ng/ml based on the usual effective range in treatment of kidney transplants, and the common adverse included Grade I‐II mucositis, hematological (neutropenia) and metabolic changes (hypercholesterolemia). Although there is no agreement of when the treatment should be stopped or how long should the patient be treated, sirolimus is another new therapeutic option for the children with BRBNS, even when other therapies have been ineffective (Gildener‐Leapman, Rosenberg, & Barmettler, ; Salloum et al, ; Triana et al, ). To improve treatment efficacy of Pulsed dye laser (PDL) in Port‐Wine Stains (PWS) of patients with Sturge–Weber syndrome (SWS) for antiangiogenic agents, a recent study demonstrated that PDL treatment in combination with topical rapamycin in the PWS of patients with SWS is more effective than laser treatment on its own (Marques et al, ).…”
Section: Sirolimus Therapy In Pediatric Overgrowth Diseasesmentioning
confidence: 99%